2008
DOI: 10.1371/journal.pone.0003759
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Detection of Colorectal Cancer in Peripheral Blood by Septin 9 DNA Methylation Assay

Abstract: BackgroundColorectal cancer (CRC) is the second leading cause of cancer deaths despite the fact that detection of this cancer in early stages results in over 90% survival rate. Currently less than 45% of at-risk individuals in the US are screened regularly, exposing a need for better screening tests. We performed two case-control studies to validate a blood-based test that identifies methylated DNA in plasma from all stages of CRC.Methodology/Principal FindingsUsing a PCR assay for analysis of Septin 9 (SEPT9)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
259
4
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 352 publications
(294 citation statements)
references
References 29 publications
16
259
4
9
Order By: Relevance
“…Bisulfite treatment and methylation specific polymerase chain reaction (PCR) are the two most commonly used techniques. A blood biomarker with a high sensitivity and specificity for CRC can not only be used to segregate high-risk patients for further clinical tests but also be an excellent tool for monitoring CRC recurrence in patients who have undergone tumor resection (Table 1) [20][21][22][23][24][25][26][27][28][29][30] .…”
Section: Biomarkers Of Dna Methylation In Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…Bisulfite treatment and methylation specific polymerase chain reaction (PCR) are the two most commonly used techniques. A blood biomarker with a high sensitivity and specificity for CRC can not only be used to segregate high-risk patients for further clinical tests but also be an excellent tool for monitoring CRC recurrence in patients who have undergone tumor resection (Table 1) [20][21][22][23][24][25][26][27][28][29][30] .…”
Section: Biomarkers Of Dna Methylation In Bloodmentioning
confidence: 99%
“…The v2 region of the Septin 9 (SEPT9) promoter has been shown to be methylated in CRC tissue compared with normal colonic mucosa. Using highly sensitive realtime PCR assays, methylated SEPT9 was first detected in the plasma of CRC patients with an overall sensitivity of 72% and a specificity of 90% [24] . Significant validation has been performed for this methylation biomarker, and Warren et al [27] have confirmed a sensitivity of up to 90% and a specificity of up to 88% for SEPT9.…”
Section: Biomarkers Of Dna Methylation In Bloodmentioning
confidence: 99%
“…Several attempts have been made in the past to search for tumour markers in the blood to develop screening tests for CRC. [7][8][9] However, validation data obtained from a large screening-eligible population are still missing or showed mitigated test performances. 10 Searching for blood-borne tumour markers could leverage different concepts such as the release of tumour-derived molecules (proteins, nucleic acids) into the blood stream, the presence of circulating tumour cells or the generation of a host response to tumour-derived signals.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic silencing of the SEPT9 gene by promoter methylation in cell-free plasma has been shown to be a biomarker for CRC [12,16,17]. Using high-sensitivity Real-Time PCR methods, hypermethylated SEPT9 DNA signatures can be detected in cellfree plasma [12,[19][20][21][22][23][24][25][26][27]. As an early event and hallmark of human cancers, aberrant DNA methylation biomarkers have clinical roles in screening, diagnosis, prognosis and therapeutic response [11,28].…”
Section: Clinicalmentioning
confidence: 99%